Association between overactive bladder and lipid accumulation product and visceral adiposity index: results from NHANES 2005–2018 - Wang, Wenhao; Tao, Anran; Xing, Ziyi; Xu, Xiaolin (Frontiers in Medicine, 2025)
BackgroundAlthough obesity is a recognized risk factor contributing to the onset and progression of overactive bladder (OAB), the existing evidence linking lipid accumulation products (LAPs) and the visceral adiposity index (VAI) to OAB remains scarce and subject to debate. Hence, this study was conducted to evaluate the associations between VAI, LAP, and the occurrence of OAB.MethodsThe information utilized in this research was sourced from the National Health and Nutrition Examination Survey (NHANES), spanning the years 2005 to 2018. The majority of the data pertaining to OAB relied on self-administered questionnaires. To assess the relationships between VAI, LAP, and OAB, we employed multivariate logistic regression models, trend analysis, and subgroup evaluations.ResultsThe study encompassed a total of 70,190 participants, with 22,928 individuals diagnosed with OAB and 5,776 serving as controls. After accounting for potential confounding factors, a statistically significant positive relationship was noted between both the visceral adiposity index (VAI) and the lipid accumulation product (LAP), as well as the occurrence of overactive bladder (OAB). Respectively, individuals in the highest quartiles of LAP and VAI demonstrated a 56% (OR = 1.555, 95% CI: 1.376–1.758) and 22% (OR = 1.225, 95% CI: 1.084–1.384) increased probability of OAB when compared to those in the lowest quartile. Additional subgroup analyses revealed that the observed associations were particularly evident in participants under the age of 60 and among women.ConclusionThis study’s findings suggest that an increase in both the visceral adiposity index (VAI) and lipid accumulation product (LAP) is associated with a greater occurrence of overactive bladder (OAB), hinting at their possible use as predictive indicators for OAB.